Bibliography on Canadian Labour History - Vaisey, G. Douglas (Labour / Le Travail, 1980)
This bibliography continues the work of the Bulletin of the Committee on Canadian Labour History in attempting to present a record of books, theses, articles, and related materials produced in the year preceding this volume (i.e., 1979). Through some warp in time, however, the Committee has yet to present the 1978 bibliography. Readers will therefore find one 1979 bibliography, one 1978 bibliography, and a third section entitled "Update in Labour Bibliography." [Note: See also the database, Canadian Labour History, 1976-2009, published at Memorial University of Newfoundland.] –Compiler's introduction